2020
DOI: 10.1136/bmjresp-2020-000716
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking status with outcomes in hospitalised patients with COVID-19

Abstract: IntroductionSmoking causes inflammation of the lung epithelium by releasing cytokines and impairing mucociliary clearance. Some studies have linked smoking with severity of illness of COVID-19 whereas others have found no such association.MethodsThis was a retrospective analysis of all adults hospitalised with COVID-19 from 9 March to 18 May 2020.Results1173 patients met the study criteria. 837 patients never smoked whereas 336 patients were either current smokers or past smoker and were grouped together in sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
(22 reference statements)
2
22
1
1
Order By: Relevance
“…The resulting profile confirms and reinforces previous studies’ results [1-5, 18, 26, 27] on COVID-19 risk factors. The profile is also consistent with the exponential increase in death risk with age, that we analyzed inferentially.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The resulting profile confirms and reinforces previous studies’ results [1-5, 18, 26, 27] on COVID-19 risk factors. The profile is also consistent with the exponential increase in death risk with age, that we analyzed inferentially.…”
Section: Discussionsupporting
confidence: 91%
“…For the boosting algorithms, the AdaBoost used 100 trees of maximum depth equal to 2, and SAMME.R algorithm, the maximum number of features when looking for the best split was set to the square root of the number of features 5 . In the case of the boosted RFs and boosted ERTs we also used 100 base estimators, each comprised of 100 trees.…”
Section: Main Results and Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning COVID-19 mortality-related risk factors, of 11 admitted patients who were current smokers in China, five did not survive ( 28 ). A more recent U.S. study found that current smokers, when compared to never smokers, were at increased risk of needing mechanical ventilation, having severe-to-critical illness, lower survival time in days, and more deaths ( 34 ). Concerning non-combustible tobacco products, a study found that 13–24-year-olds who engaged in exclusive e-cigarette use and dual-use of e-cigarettes and combustible cigarettes were at significantly increased odds to have positive COVID-19 diagnoses, while accounting for clustering by U.S. states and regions ( 35 ).…”
Section: Tobacco Use and Covid-19mentioning
confidence: 99%
“…The first group are smokers; cigarette smoke has been reported to lead to an enhanced risk of inflammatory and autoimmune diseases [14]. Smokers are more likely to develop critical COVID-19 requiring mechanical ventilation [15] that might lead to a higher mortality rate [16,17]. Interestingly, alarms about the danger of misreading non-significant or inconclusive frequentist results containing several possible biases of a contradictory hypotheses have been raised [18,19].…”
Section: Could High Risk Groups Lower the Chances To Develop Autoimmumentioning
confidence: 99%